Food security and the threat from within : rice policy reforms in the Philippines - Tolentino, Bruce (2009)
The forces of globalization, in tandem with realities of domestic natural resources, economics and politics, and the influence of international institutions such as the World Trade Organization (WTO), Association of Southeast Asia Nations (ASEAN) and the Asian Development Bank (ADB), are re-shaping the food security policy and strategy of nations such as Philippines. This paper describes the forces that have come to bear on the shaping of food security policy in the Philippines in recent years, and the Philippine Government's responses to the challanges. This paper attempts two approaches to the problem.